The Difference in The Education Curriculum System of Asean Member States: Indonesia and Singapore - Ikhsanuddin, Muhammad; Sukari, Sukari (UNIVERSITAS SERAMBI MEKKAH, 2025)
Education is one of the most important components of life. Since humans began engaging in educational activities, they have successfully realized various developments and advancements in all aspects of their lives. Generally, the process of education has also experienced significant progress, both in terms of methods and the goals to be achieved. The Indonesian government has consistently worked to improve the quality of education by implementing various changes in the education sector, with the curriculum serving as a key tool for enhancing educational quality. Differences in curriculum systems provide a way to understand various aspects related to the education systems of Indonesia and Singapore. This research is qualitative in nature, employing a descriptive method. The author collected data from journals, books, and online media. The study utilizes the theory of differences in curriculum systems. The aim of this research is to identify the differences in the education curriculum systems between Indonesia and Singapore. In conclusion, education is crucial for both developed and developing countries. For developed countries like Singapore, the education curriculum is used as an effort to continuously improve the quality of life for its citizens. Meanwhile, for developing countries like Indonesia, the education curriculum is implemented as an effort to catch up with more advanced nations.